2022
DOI: 10.1155/2022/4672535
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Peripheral Blood DCs CD86, CD80, and Th1/Th2 in Sepsis Patients and Their Value on Survival Prediction

Abstract: Objective. To explore the expression of peripheral blood dendritic cells (DCs) CD86, CD80, and Th1/Th2 in patients with sepsis and their value on survival prediction. Methods. 118 patients with sepsis from January 2019 to December 2020 were selected, According to the prognosis, the patients were divided into the death group ( n = 46 ) and survival group ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…CD4 + CD25 + Foxp3 + Tregs represent a natural Treg subset that mainly exerts an immunosuppressive effect through cell contact (Chen et al 2021 ). CD86 is an immunoglobulin expressed by antigen-presenting cells and is involved in T lymphocyte proliferation and activation (Du et al 2022 ). PD-L1 is a negative regulator of T and B cells and plays an important role in mediating lymphocyte tolerance to self-antigens (Chen et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + CD25 + Foxp3 + Tregs represent a natural Treg subset that mainly exerts an immunosuppressive effect through cell contact (Chen et al 2021 ). CD86 is an immunoglobulin expressed by antigen-presenting cells and is involved in T lymphocyte proliferation and activation (Du et al 2022 ). PD-L1 is a negative regulator of T and B cells and plays an important role in mediating lymphocyte tolerance to self-antigens (Chen et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…S4A, B). CD80 is a marker of DC activation [ 42 ], and further analysis revealed that the infiltration rate of CD80 + DCs in VNP-shCCDC25-treated mouse metastases was 10.8%, which was significantly greater than the infiltration rates in PBS-treated (8.7%) and VNP-NC-treated (5.3%) cells (Fig. 7 A, B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in response to microbial components, DCs from hosts with polymicrobial sepsis exhibit maturation defects, have an impaired ability to produce interleukin (IL)-12 and secrete high levels of IL-10 [ 4 , 5 ]. This functional reprogramming of DCs may contribute to immunoparalysis and poor prognosis in patients with infection [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%